2022
DOI: 10.1021/acsami.2c01981
|View full text |Cite
|
Sign up to set email alerts
|

Role of Terminal Group Position in Triphenylamine-Based Self-Assembled Hole-Selective Molecules in Perovskite Solar Cells

Abstract: The application of self-assembled molecules (SAMs) as a charge selective layer in perovskite solar cells has gained tremendous attention. As a result, highly efficient and stable devices have been released with stand-alone SAMs binding ITO substrates. However, further structural understanding of the effect of SAM in perovskite solar cells (PSCs) is required. Herein, three triphenylamine-based molecules with differently positioned methoxy substituents have been synthesized that can self-assemble onto the metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 65 publications
(116 reference statements)
0
20
0
Order By: Relevance
“…It was found that the para-and ortho-substituted SAMs enabled the formation of a perovskite thin film with large grains grown atop, increasing the PCE to 20%. 50, 51 Zhang et al 52 54 The MPA-BT-CA-based SAMs could induce intramolecular charge transfer and contribute to fast hole extraction and reduce the charge recombination rate in PSCs, which achieved a PCE of 21.24%. Additionally, MPA-BT-CA also displayed a good performance in eco-friendly alcohol solvent with a PCE of 20.52%.…”
Section: Passivation Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the para-and ortho-substituted SAMs enabled the formation of a perovskite thin film with large grains grown atop, increasing the PCE to 20%. 50, 51 Zhang et al 52 54 The MPA-BT-CA-based SAMs could induce intramolecular charge transfer and contribute to fast hole extraction and reduce the charge recombination rate in PSCs, which achieved a PCE of 21.24%. Additionally, MPA-BT-CA also displayed a good performance in eco-friendly alcohol solvent with a PCE of 20.52%.…”
Section: Passivation Effectmentioning
confidence: 99%
“…It was found that the para - and ortho -substituted SAMs enabled the formation of a perovskite thin film with large grains grown atop, increasing the PCE to 20%. 50,51 Zhang et al 52 introduced three SAMs with different numbers of F atoms ( 40–42 ) in phenylacetic acid to modify the surface work function (WF) of the ITO substrate with the formation of interfacial dipoles. Due to the optimized band structure and lower energy loss at the ITO/MAPbI 3 interface, the 2TFA-modified device achieved the highest power conversion efficiency (PCE) of 20.19%.…”
Section: Sams As Hole Transport Layers or Modifying Layers For P–i–n-...mentioning
confidence: 99%
“…However, the holes in the thin film disappeared and the surface morphology became uniform when increasing the annealing temperature close to the T g of the HTMs (Figure b–e). It is well-known that trace residue solvents in the thin film can damage the morphology and quality of the films. , Under low annealing temperature ( T annealing ≪ T g ), the residual solvent is evaporated first, and molecules tend to agglomerate to fill the gaps, thereby resulting in tiny holes in the film. , This is a kinetic control process since molecular motion is significantly suppressed during the low-temperature annealing process. Increasing the annealing temperature gradually to the T g ( T annealing ≈ T g ) with a thermal control process (Figure a ), the intensified molecular thermal motion makes the molecules rearrange and fills the tiny holes that were induced by the residue solvent volatilization, resulting in a much better surface morphology .…”
Section: Molecular Design Synthesis and Characterizationmentioning
confidence: 99%
“…The viability of this concept was first demonstrated by Magomedov et al They used carbazole derivatives (known as PACz series) with phosphonic acid anchoring groups which spontaneously adsorb onto the surface of metal oxide substrates to form a conformal monolayer. Since then, several molecules with further structural modifications have been reported to function as hole-collecting monolayers. All these structures are composed of a π-conjugated backbone connected to a single anchoring group. When chemically adsorbed, these monopodal molecules tend to orient with their π-plane perpendicular (edge-on) to the metal oxide surface. , This molecular alignment could result in inefficient orbital overlap with the perovskite surface and/or unsought hole transport in the lateral direction, causing undesired interfacial recombination and interfering with the hole extraction process (Figure a). ,, …”
Section: Introductionmentioning
confidence: 99%